2012
DOI: 10.1038/onc.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

Increased invasiveness of MMP-9-deficient tumors in two mouse models of neuroendocrine tumorigenesis

Abstract: Despite their apparent success in pre-clinical trials, metalloproteinase (MMP) inhibitors proved to be inefficacious in clinical settings. In an effort to understand the underlying causes of this unanticipated outcome, we modeled the consequences of long-term MMP inhibition by removing one of the major players in tumorigenesis, MMP9, in two complimentary mouse models of pancreatic neuroendocrine carcinogenesis: Myc;BclXl and RIP1-Tag2. By employing gel zymography and a fluoregenic solution assay, we first esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 68 publications
2
38
0
Order By: Relevance
“…Previous reports suggest a mechanism through which resistance to MMP inhibitors involves elevated cathepsin activity, dependent on a change in the abundance of inflammatory cells supplying these proteases (Shchors et al 2013). Thus, our data share parallels with these results and show that deletion of multiple cathepsin proteases can conversely alter MMP expression, possibly via perturbation of the protease web.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Previous reports suggest a mechanism through which resistance to MMP inhibitors involves elevated cathepsin activity, dependent on a change in the abundance of inflammatory cells supplying these proteases (Shchors et al 2013). Thus, our data share parallels with these results and show that deletion of multiple cathepsin proteases can conversely alter MMP expression, possibly via perturbation of the protease web.…”
Section: Discussionsupporting
confidence: 80%
“…2B). Interestingly, CtsZ deletion significantly decreases RT2 tumor invasion (Akkari et al 2014), while Mmp9 ablation has been reported to unexpectedly promote tumor invasion in two independent PanNET mouse models (Shchors et al 2013), including the RT2 model used in this study. Other MMPs, including Mmp3 and Mmp13, have been implicated in the regulation of tumor development and invasion (Kessenbrock et al 2015); however, there have been no correlative studies linking these two MMPs with PanNET malignancy.…”
Section: Combined Deletion Of Ctsb and Ctss Reduces Angiogenic Switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic models that recapitulate the heterogeneity and multistage nature of tumor progression are believed to be more predictive than xenograft models (14). Interestingly, genetic mouse models of neuroendocrine pancreatic cancer recently demonstrated that the ablation of MMP-9 gave rise to more invasive tumors (15). However, neuroendocrine tumors of the pancreas are a relatively rare condition, accounting for only 1% to 5% of the diagnosed pancreatic cancers, while the large majority of tumors are PDACs, arising from the exocrine cellular compartment (1).…”
Section: Introductionmentioning
confidence: 99%
“…For example, enhanced invasion of MMP-9-deficient tumours is associated with homing of cathepsin B-expressing leukocytes to invasive tumour fronts, facilitating invasion (Shchors et al, 2013). Finally, inefficacy of protease inhibitors may be due to non-proteolytic roles of proteases such as their interaction with other proteins (Kessenbrock et al, 2015).…”
Section: Proteases In Stromal Cellsmentioning
confidence: 99%